First-in-man, first-in-class phase I study with the monopolar spindle 1 kinase inhibitor S81694 administered intravenously in adult patients with advanced, metastatic solid tumours. (July 2022) - Schöffski, Patrick; Awada, Ahmad; de la Bigne, Anne-Marie; Felloussi, Zakia; Burbridge, Mike; Cantero, Frederique; Colombo, Riccardo; Maruzzelli, Sara; Ammattatelli, Katia; de Jonge, Maja; Aftimos, Philippe; Dumez, Herlinde; et al.
Abstract: Background: S81694 is an inhibitor of monopolar spindle 1 kinase, a target expressed in proliferating cells. CL1-81694-001 was the first-in-human study aiming at identifying a safe dosing schedule in solid tumour patients. Patients and methods: This trial was based on inter-individual dose-escalation of single agent S81694 in cohorts of ≥3 patients to assess the safety and tolerability and determine dose-limiting toxicities (DLTs), maximum tolerated dose (MTD) and recommended phase II dose (RP2D), with S81694 given on days 1, 8, 15 of a 28-day cycle as 1-h infusion. Results: 38 patients were treated at doses ranging from 4 to 135 mg/m 2 /week; 144 cycles were administered (median 2/patient; range 1–32 cycles). Patients discontinued treatment for disease progression (78.9%), adverse events (AE; 18.4%) or withdrawal of consent (2.6%). Treatment modifications occurred in 22 patients (57.9%; 49 cycles). Common treatment-emergent AEs were fatigue (22 patients;57.9%), anaemia (17;44.7%) and nausea (12;31.6%). Haematological toxicity was mild, with Grade 3 anaemia observed in three patients and neutropenia mainly seen at the 135 mg/m 2 dose level. Three first cycle DLTs included G3 anaemia (4 mg/m 2 dose), G4 hypertension (20 mg/m 2 ), G3 fatigue (135 mg/m 2 ). MTD was not reached due to premature discontinuation of enrolment based on a sponsor decision. Among 35 patients evaluable for response, one (renal cell carcinoma) had a complete response, one (hepatocellular carcinoma) had a transient decrease of target lesions and 13 had stable disease. Seven patients remained on study for ≥6 cycles, two at the 135 mg/m 2 dose. Conclusions: S81694 can be administered safely as a single agent in adults with solid tumours on days 1, 8, 15 of a 28-day cycle up to a dose of 135 mg/m 2 /week without reaching MTD. The RP2D was not defined due to the prioritization of the use of S81694 in combination with cytotoxic agents, based on emerging preclinical data. Trial registration: EudraCT number: 2014-002023-10; ISRCTN registry ISRCTN35641359. Highlights: First trial with monopolar spindle 1 kinase inhibitor in solid tumour patients. MTD not reached when exploring doses up to 135 mg/m2/week. Well tolerated and early signs of anti-tumour activity. Further development warranted, ideally in combination with other drugs.